Visual Identity of Malaysian Modern Sculpture - Abdul Halim Husain (Journal of Visual Art and Design, 2013)
An artwork is the manifestation of an artist's utilization of a variety of approaches, which is closely related to the idea of an artist, media and technique. The manipulation of an artwork is based on the relationship of an artist, idea and media, through formalistic approaches and the surrounding community. Understanding of the visual identity is related to other disciplines in fine art, such as painting, printing and drawing, and new media because of the nature of its context, which is based on the physical form and space. The aim of this research is to generate knowledge on visual identity through sculpture. The research explores the forms and the symbolic meanings based on the influence of the local community and social system. This study employs the cultural concept as a system to create an understanding framework to the process of creating artwork. The qualitative approach is used as the methodology framework, which is deemed as suitable to the problem of investigating the visual identity in sculptures. The findings uncover that Malaysian sculptures synergize harmoniously the value system with modern expression, through belief, surroundings, needs and social requirements. These findings contribute to the knowledge of art, generally, that can be used in other fields of art in the process of creation and appreciation.